SANGGIT TOKOH DALAM BANJARAN SENGKUNI - Triyogo, YB Rahno (Acintya, 2018)
Banjaran Sengkuni is a play that tells the story of the life of a wayang character named Sengkuni, from his birth to tragic death. Through the play the puppeteer believes that the real character of a figure is formed not only from birth but also since the process of fetal occurrence through sexual intercourseof the parents. Besides the process in the womb, the character is also formed by the environment that surrounds its life: the environment of the family, the surrounding community, and the universe.The character of Sengkuni in Banjaran Sengkuni was largely determined by the process of development of the baby or fetus in the womb, namely through the results of adultery or adultery which is culturally considered negative, even sin. He inherited his father’s character, Gandarwa named Setibar. The characters which could be observed include: baby Sengkuni was born with a handsome face but fanged, just like his father having fangs. In wayang tradition, a fang reflects a negative value.Keywords:character, fetal formationprocess, environment, universe